Inclusive Premarital Education for Persons with Disabilities: Legal Reform and Lifelong Learning Perspectives in Indonesia - Fahrur Rozi; Fadil Fadil; Burhanuddin Susamto; Niela Agustin Hermawatie; Anna Sakreti Nawangsari (AL-ISHLAH: Jurnal Pendidikan, 2025)
Premarital education serves as a strategic tool to foster sustainable and equitable family life. However, in Indonesia, people with disabilities often face exclusion from such programs due to legal and pedagogical frameworks that lack inclusivity. This research addresses the gap between the normative commitment to non-discrimination and the practical implementation of premarital education. This study employs a qualitative, normative-juridical and socio-legal approach, using legal documents, policy analyses, and literature reviews. It integrates the principles of inclusive education, adult learning, and lifelong education to evaluate the current state of premarital education in Indonesia and its accessibility for persons with disabilities. Findings show that existing legal frameworks, such as Law No. 8/2016 on Persons with Disabilities and Law No. 1/1974 on Marriage, guarantee equal rights, yet premarital education guidelines remain largely non-adaptive. Key issues include the absence of inclusive curriculum design, a lack of trained facilitators, and minimal use of accessible media such as Braille, sign language, or audio materials. This study highlights the need for legal reconstruction to incorporate inclusive practices into premarital education policy. By aligning legal provisions with the principles of Universal Design for Learning and maqāṣid al-sharī‘ah, premarital education can evolve into a non-formal, lifelong learning platform that promotes equality and dignity for all citizens, including persons with disabilities.